2023
DOI: 10.1063/5.0157802
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on supercavitation in jet pump cavitation reactors for zero flow-ratio conditions

Abstract: We report an experimental study of cavitating flow in a jet pump cavitation reactor (JPCR) with a special emphasis on the supercavitation stage with a tubular supercavitation cavity. This study focuses on the evolution and characteristics of the cavitation for the zero flow-ratio conditions and the supercavitation mechanism. The results show that increasing the limiting flow ratio qr leads to shearing cavitation, which transforms into supercavitation when qr = 1. A cloud cavity forms at the end of the tubular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Hydrodynamic cavitation is a transient phase transition phenomenon [2] , [3] , [4] . At the beginning, scholars' research on hydrodynamic cavitation mainly focused on how to reduce the negative effects of cavitation on centrifugal pumps, ship propellers, and other mechanical equipment such as erosion, vibration, and noise [5] , [6] , [7] , [8] . However, with the deepening of study, researchers have found that the huge energy generated by the collapse of cavitation bubbles can break the chemical bonds of water molecules and produce hydroxyl radicals (•OH) with strong oxidation, which has been effectively applied in the fields of biodiesel preparation, organic degradation of wastewaters, chitosan nanoparticle synthesis, and so on [9] , [10] , [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamic cavitation is a transient phase transition phenomenon [2] , [3] , [4] . At the beginning, scholars' research on hydrodynamic cavitation mainly focused on how to reduce the negative effects of cavitation on centrifugal pumps, ship propellers, and other mechanical equipment such as erosion, vibration, and noise [5] , [6] , [7] , [8] . However, with the deepening of study, researchers have found that the huge energy generated by the collapse of cavitation bubbles can break the chemical bonds of water molecules and produce hydroxyl radicals (•OH) with strong oxidation, which has been effectively applied in the fields of biodiesel preparation, organic degradation of wastewaters, chitosan nanoparticle synthesis, and so on [9] , [10] , [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%